Hydrogen embrittlement resistance of precipitation-hardened FeCoNiCr high entropy alloys. (February 2023) - Zhang, Fan; Lu, Bairu; Liu, Xiongjun; Wang, Hui; Jiang, Suihe; Naeem, Muhammed; Wang, Xun-Li; Wu, Yuan; Lu, Zhaoping
Abstract: Precipitation-hardened high-entropy alloys (HEAs) with coherent nanoprecipitates are considered promising candidates for structural application as they have shown a unique combination of high strength and good ductility. Nevertheless, the hydrogen embrittlement resistance of this kind of alloy remains unclear, which prevents the precipitation-hardened HEAs from practical uses in the environment with existence of hydrogen. In this work, we systematically investigated the influences of hydrogen on the mechanical properties and deformation behavior of a series of Fe–Co–Ni–Cr precipitation-hardened HEAs. Our results demonstrated that the hydrogen penetrating into precipitation-hardened HEAs can enhance localized plastic deformation and cause stress concentration near the fracture, but the response of mechanical properties is closely related to the number of nanoprecipitates. In the precipitation-hardened HEAs with a proper amount of nanoprecipitates, the localized plastic deformation promoted the formation of deformation twinning which relieved stress concentration and enhanced the strength and ductility concurrently. In those with excessive nanoprecipitates, however, the fracture process was accelerated and hydrogen embrittlement occurred with decreased ductility due to the increased critical twinning stress resulted from the small interspaces between precipitates. Our findings are helpful not only for understanding the hydrogen embrittlement mechanism in complex alloys, but also for the future design of high-performance HEAs with good hydrogen embrittlement resistance. Highlights: Two kinds of trap sites for hydrogen atoms are detected in precipitation-hardened HEAs. Systematic study on influences of hydrogen on mechanical properties and deformation behavior. Hydrogen penetrating into alloys enhanced localized plastic deformation. Hydrogen embrittlement resistance is closely related to the number of precipitates.